DIFFUSE B-LARGE CELL LYMPHOMA OF TERMINAL ILEUM - CASE REPORT - Tešić, Miloš (Halo 194 Scientific Journal of Emergency Medicine, 2025)
Diffuse large B-cell lymphoma (DLBCL) of the gastrointestinal tract represents the most common form of extranodal manifestation of this disease. Due to the abundance of lymphoid tissue, the terminal ileum is particularly prone to lymphoma development. The clinical presentation is often nonspecific, most commonly involving gastrointestinal hemorrhage or perforation, while obstruction is less frequent. This paper presents the case of an 80-year-old patient in whom obstruction was the initial manifestation of the disease. The diagnosis was established through endoscopy and histopathological analysis, and the patient was treated surgically and with chemoimmunotherapy. Despite treatment, complications occurred in the form of neutropenia, urinary infection, and ultimately a fatal outcome.
Keywords: diffuse large B-cell lymphoma, terminal ileum, obstruction